Organizations and institutions : sociological and economic approaches to the analysis of social structure - Winship, Christopher; Rosen, Sherwin ([Chicago] : University of Chicago Press, 1988)
A supplement of the "American Journal of sociology, volume 94, supplement 1988." It analyzes the effects of a number of schemes on productive work versus unproductive competition.
"American Journal of sociology, volume 94, supplement 1988."
Includes bibliographical refeences.
hza 29/01/2019
Loans
Keywords: Social institutions; Economics